Optimizing the @official.usu Instagram Account to Improve the Institution's Image - Afifah, Tsani; Masril, Munzaimah (Jurnal Network Media, 2024)
This article is entitled "Optimizing the @official.usu Instagram Account to Improve the Image of the Institution." This study aims to determine the level of effectiveness of using Instagram @official.usu in improving the image of the University of North Sumatra when measured using the EPIC model. So, the theory used is the EPIC model. The research method is descriptive-quantitative. The population in this study was 100 thousand followers of the @official.usu Instagram account, with a sample size of 100 followers determined using the Slovin formula with a margin of error of 10%. Data collection was carried out using a questionnaire. The data analysis used is descriptive statistical analysis and the calculation of average scores, which includes calculating the cumulative score of each dimension of the EPIC model and the calculation of the EPIC rate. The results showed that the use of Instagram @official.usu was effective in improving the image of the University of North Sumatra based on the calculation of the EPIC rate, which was carried out by calculating the average value of the cumulative score of the four dimensions of the EPIC model. The calculation obtained a score of 4.17, included in the effective scale range. So, it can be stated that based on the dimensions of empathy, persuasion, impact, and communication, the use of Instagram @official.usu is effective in improving the image of the University of North Sumatra institution.